(untitled) (Journal of New Zealand Grasslands, 2025)
Northland’s subtropical climate presents both challenges and opportunities for pasture systems under future climate scenarios. This study aimed to identify C4 grasses and subtropical legumes with potential to improve resilience, productivity, and sustainability of Northland pastures. Candidate species were compiled from historical Northland trials and the Tropical Forages database, resulting in an initial pool of 60 grass and over 90 legume taxa. Each species was assessed for agronomic potential, availability of seed or cultivars, and regulatory status under the MPI Plant Biosecurity Index. Nomenclature was standardised using authoritative taxonomic databases. Species were classified into three categories—Green, Orange, and Red—based on priority for evaluation. Green list species are both agronomically promising and permitted by MPI, while Orange list species have limitations requiring further consideration. Red list species are either restricted, unrecorded, or deemed agronomically unsuitable. Cultivar availability and breeding activity were highly variable, with legume options especially constrained. A staged approach to evaluation is recommended, including initial use of nitrogen fertiliser in legume trials to defer rhizobium-specific work. This review highlights the need for renewed trialling of selected subtropical species and supports a pathway toward diversifying pasture systems in warmer regions of New Zealand.